Preparation method and application of cross-linked ligand modified perovskite quantum dots

By using amber-2- (methyl acryseyl oxygenyl) ethyl (MMES) as a ligand to modify the perovskite quantum point, and the optical agglomeration reaction with the polymer monitors, prepare CSPBBR3/polymer HDDA composite Things solve the problem of uneven distribution and degradation in the polymers of perovskite quantum dots in the polymer, and realize its stability and efficient lighting performance at water and heat.

CN119351094APending Publication Date: 2025-01-24LANZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411261031.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Perovskite quantum dots are prone to degradation under water environment, oxygen, ultraviolet rays, heat, and polar organic solvents, resulting in uneven distribution in polymers, resulting in a decrease in luminous intensity or no longer luminous.

Method used

Using amber-2- (MMES) as a ligand with olty-iltic ore ore is used as a ligand, CSPBBR3 perovskite is used to grow through the room temperature ligand assistance and re-precipitate. The quantum dot and the optical polymerization aggregation reaction with the polymerization of the acrylic acid to prepare the CSPBBR3/polymer HDDA complex.

Benefits of technology

Through the reaction of ligand modification and optical aggregation, the decentralization and stability of the perovskite quantum dot in the polymer is significantly improved, it enhances its stability to water and thermal, and improves the strength and thermal quenching performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119351094A_ABST
    Figure CN119351094A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of luminescent materials, and particularly discloses a preparation method of a cross-linked ligand modified perovskite quantum dot, and the cross-linked ligand modified perovskite quantum dot is prepared by taking succinic acid mono-2-(methacryloyloxy) ethyl ester (MMeS) as a ligand of the perovskite quantum dot and utilizing a room-temperature ligand-assisted reprecipitation method. Injecting the cesium-lead precursor solution into a xylene solution to grow CsPbBr3 perovskite quantum dots modified by a functional ligand MMeS; then carrying out a photopolymerization copolymerization reaction by using a methacrylate group in the MMeS molecule and an acrylate polymer monomer 1, 6-hexanediol diacrylate (HDDA), so as to obtain a CsPbBr3 / poly-HDDA compound; the invention also provides application of the product obtained by the method. The stability of the CsPbBr3 quantum dot is improved through modification of mono-2-(methacryloyloxy) ethyl succinate, and the stability of the quantum dot is further improved through the CsPbBr3 / poly-HDDA compound.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of luminescent materials, and in particular relates to a preparation method of cross-linked ligand-modified perovskite quantum dots and applications thereof. Background Art

[0002] Cesium lead halide perovskite quantum dots (PQDs) have excellent optical properties such as high color purity, easily tunable photoluminescence emission wavelength, and high quantum yield, and have shown great application potential in optoelectronic display fields such as white light emitting diodes (LEDs) and micro-LED displays. However, the inherent ionic properties and low formation energy of PQDs make them prone to degradation in water environments, oxygen, ultraviolet rays, heat, and polar organic solvents, hindering the application of this material. To solve this problem, the stability of quantum dots can be improved by generating PQDs / polymer composites.

[0003] Studies have shown that polymers can be dissolved in organic solvents to make polymer solutions, and then PQDs (or precursors of PQDs) can be mixed with the polymer solution, and the organic solvent can be evaporated to prepare a PQDs / polymer complex; or PQDs (or precursors of PQDs) can be mixed with polymer monomers, and the PQDs / polymer complex can be prepared after monomer polymerization. However, since PQDs have fewer functional groups that interact with polymer matrix molecules and are prone to phase separation, PQDs will be unevenly distributed or aggregated in the polymer, resulting in severe self-absorption quenching, causing the luminescence intensity of PQDs / polymer to decrease or even stop emitting light. Therefore, it is extremely important to establish effective chemical bond interactions between perovskite quantum dots and polymers, improve the dispersibility of perovskite quantum dots in polymers, and improve the stability of perovskite quantum dots to water and heat, which is extremely important for the application of perovskite quantum dots in the fields of wide color gamut LED backlight display and Micro-LED display. Summary of the invention

[0004] The first object of the present invention is to overcome the above problems and to provide a method for preparing perovskite quantum dots which are uniformly distributed in a polymer and modified with cross-linked ligands that are stable to water and heat.

[0005] The second object of the present invention is to provide perovskite quantum dots obtained according to the above method.

[0006] The third object of the present invention is to provide applications of the above-mentioned perovskite quantum dots.

[0007] The purpose of the present invention is specifically achieved through the following technical solutions:

[0008] A method for preparing cross-linked ligand-modified perovskite quantum dots, using a functional molecule mono-2-(methacryloyloxy)ethyl succinate (MMeS) containing carboxyl and methacrylate groups as a ligand of the perovskite quantum dots, injecting a cesium lead precursor solution into a xylene solution using a room temperature ligand-assisted reprecipitation method to grow CsPbBr3 perovskite quantum dots modified with the functional ligand MMeS; and then using the methacrylate groups in the MMeS molecules to undergo a photopolymerization copolymerization reaction with an acrylic ester polymer monomer 1,6-hexanediol diacrylate (HDDA) to prepare a CsPbBr3 / poly-HDDA complex.

[0009] Furthermore, the method comprises the following steps:

[0010] (1) Preparation of CsPbBr3 perovskite quantum dots modified with functional ligands

[0011] 1.1) adding cesium bromide, lead bromide, oleylamine and succinic acid mono-2-(methacryloyloxy)ethyl ester to N,N-dimethylformamide and stirring until the powder is completely dissolved to prepare a precursor solution;

[0012] 1.2) Inject the precursor solution into a continuously stirred xylene solution to obtain a bright green solution;

[0013] 1.3) After the solution obtained in step 1.2) is stirred for reaction, methyl acetate is added to generate a precipitate, and the precipitate is dispersed in xylene by centrifugation. The supernatant is collected by centrifugation to obtain a xylene solution of CsPbBr3 quantum dots modified with MMeS;

[0014] (2) Preparation of CsPbBr3 / poly-HDDA complex by copolymerization of ligand and monomer

[0015] The MMeS-modified CsPbBr3 quantum dot xylene solution obtained in step 1.3) was uniformly mixed with 1,6-hexanediol diacrylate, and diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide was added. Under stirring and nitrogen atmosphere, the solution was continuously irradiated with 365 nm ultraviolet light to obtain a CsPbBr3 / poly-HDDA composite solid.

[0016] Preferably, in step 1.1), the usage ratio of cesium bromide, lead bromide, oleylamine, mono-2-(methacryloyloxy)ethyl succinate, and N,N-dimethylformamide is 50-100 mg: 100-150 mg: 0.5-1 ml: 0.5-2 mmol: 5-10 mL.

[0017] Preferably, in step 1.2), the volume ratio of the precursor solution to the xylene solution is 0.5-1:5-10.

[0018] Preferably, in step 1.3), the stirring reaction time is 40 min; the volume ratio of ethyl acetate to xylene in step 1.2) is 1:1; the centrifugal speed is 12000 r / min when separating the precipitate, and the centrifugal speed is 8000 r / min when collecting the MMeS-modified CsPbBr3 quantum dot xylene solution.

[0019] Preferably, in step (2), the volume ratio of the MMeS-modified CsPbBr3 quantum dot xylene solution to 1,6-hexanediol diacrylate is 4:1, the amount of diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide is 1% of the mass of 1,6-hexanediol diacrylate; the intensity of the ultraviolet light is 3 mW / cm 2 The UV light irradiation time is 0.5 to 2 minutes.

[0020] The MMeS-modified CsPbBr3 perovskite quantum dots and CsPbBr3 / poly-HDDA complexes obtained by the above method.

[0021] Application of CsPbBr3 / poly-HDDA complex in white light LEDs, and application of MMeS-modified CsPbBr3 perovskite quantum dots in electrofluidic inkjet-printed perovskite micro-pattern arrays.

[0022] (1) CsPbBr3 / poly-HDDA complex was reacted with red phosphor KSF (K2SiF6:Mn 4+ ) is mixed with UV curing glue and dripped onto a 460nm blue light LED chip. The mixture is cured under UV light to produce a white light LED.

[0023] (2) MMeS-modified CsPbBr3 quantum dots are mixed with HDDA and n-dodecane to prepare an ink for electrofluidic inkjet printing. The ink can be used to print a perovskite micro-pattern array, which can effectively improve the hydrothermal stability of each pixel after UV curing.

[0024] The present invention uses a functional molecule succinic acid mono-2-(methacryloyloxy)ethyl ester (MMeS) containing both carboxyl and methacrylate groups as a ligand of perovskite quantum dots. The carboxyl group on the ligand is first firmly combined with the perovskite quantum dots through a coordination bond, and then the methacrylate group contained in the ligand undergoes a copolymerization chemical reaction with an acrylate monomer. The quantum dots are strung on the molecular chain of the generated polymer through the ligand, which effectively reduces the aggregation of the perovskite quantum dots in the polymer, reduces the shedding of the ligand on the surface of the perovskite quantum dots, and gives the quantum dots good luminescence stability and thermal quenching performance. In addition, the physical barrier formed by the polymer can also better protect the perovskite quantum dots, significantly improving the water stability of the perovskite quantum dots. The reaction system is irradiated with 365nm ultraviolet light to induce the generation of free radicals; the polymerization reaction is carried out in a nitrogen-filled atmosphere to prevent oxygen and moisture in the air from quenching the free radicals in the polymerization reaction.

[0025] Compared with the prior art, the present invention has the following advantages:

[0026] (1) Using mono-2-(methacryloyloxy)ethyl succinate (MMeS) as a ligand for perovskite quantum dots, the carboxyl group in the ligand can interact with the perovskite quantum dots and passivate the surface defects of the quantum dots, thereby preliminarily improving the stability of the quantum dots;

[0027] (2) The perovskite quantum dots modified with MMeS were photoinitiated to copolymerize with 1,6-hexanediol diacrylate (HDDA) monomer to generate CsPbBr3 / poly-HDDA complex. The photoinitiated polymerization reaction has the advantages of simple operation and low energy consumption, and the stability of CsPbBr3 quantum dots was further effectively improved after copolymerization.

[0028] (3) The raw material MMeS is a commercial product, the raw material is easily available, and the ligand-assisted reprecipitation method is used to prepare perovskite quantum dots, which makes the process conditions for preparing quantum dots mild and the operation simple, making it easy to mass-produce quantum dots;

[0029] (4) The raw material HDDA is a commercial product. Using MMeS-modified CsPbBr3 quantum dots and HDDA as the ink for electrofluidic inkjet printing can easily achieve a stable perovskite micro-pattern array, which is beneficial to the application of CsPbBr3 quantum dots in Micro-LED display. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 is a gel chromatography test chart of the reaction product in Example 1 of the present invention;

[0031] Figure 2 It is a comparison chart of the XRD spectrum of the perovskite light-emitting material in Examples 2-4 of the present invention and the standard PDF card;

[0032] Figure 3 The transmission electron microscope images (left column) and high-resolution transmission electron microscope images (right column) of the perovskite light-emitting materials in Examples 2-4 of the present invention are shown;

[0033] Figure 4 is the normalized fluorescence emission spectrum of the perovskite luminescent material in Examples 2-4 of the present invention;

[0034] Figure 5 is the change in normalized fluorescence emission intensity over time when the perovskite light-emitting material in Example 2-4 of the present invention is immersed in water;

[0035] Figure 6 is the change of the normalized fluorescence emission intensity as a function of the heating temperature when the perovskite light-emitting material is heated in Examples 3 and 4 of the present invention;

[0036] Figure 7 This is the electroluminescence spectrum of the white light LED lamp bead in Test Example 1 of the present invention;

[0037] Figure 8 is the color coordinate diagram of the white light LED lamp bead in Test Example 1 of the present invention;

[0038] Fig. 9 This is a photo of the perovskite micro-pattern of "Lanzhou University" in Test Example 1 of the present invention;

[0039] Fig.10 This is a photo of the “frog” perovskite micro-pattern in Test Example 1 of the present invention. DETAILED DESCRIPTION

[0040] The preferred embodiments of the present invention are described below. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0041] Unless otherwise specified, the raw materials in the examples of the present invention were purchased through commercial channels, and the sources of some of the raw materials are as follows: mono-2-(methacryloyloxy)ethyl succinate (MMeS) (McLean, 95%), 1,6-hexanediol diacrylate (HDDA) (McLean, 90%), and diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide (McLean, 97%).

[0042] Example 1

[0043] This embodiment provides an MMeS trimer, and the preparation method thereof comprises the following steps: in a nitrogen atmosphere, using 3 mW / cm 2 The xylene solution of MMeS was irradiated with 365 nm ultraviolet light for 60 min to obtain MMeS trimer.

[0044] Example 2

[0045] The present embodiment provides a CsPbBr3 quantum dot modified with MMeS, and the preparation method thereof comprises the following steps: 85 mg of cesium bromide (CsBr), 146 mg of lead bromide (PbBr2), 0.5 ml of oleylamine (OAm) and 2 mmol of mono-2-(methacryloyloxy)ethyl succinate (MMeS) are added to 10 mL of N,N-dimethylformamide (DMF), and magnetic stirring is continued at 500 r / min until the powder is completely dissolved to obtain a precursor solution. Subsequently, 0.5 ml of the clarified precursor solution is extracted, and 10 ml of xylene solution is injected under continuous stirring to obtain a bright green solution; after stirring the reaction for 40 min, 10 ml of methyl acetate as a precipitant is added, and centrifuged at 12000 r / min for 5 min, the resulting precipitate is dispersed in 2 ml of xylene, and the supernatant is collected after centrifugation at 8000 r / min for 3 min to obtain a xylene-dispersed MMeS-modified CsPbBr3 quantum dot solution (denoted as M-CPB).

[0046] Example 3

[0047] This embodiment provides a CsPbBr3 quantum dot modified with a MMeS trimer, and the preparation method thereof comprises the following steps: in a nitrogen atmosphere, using 3 mW / cm 2 The CsPbBr3 quantum dot solution prepared in Example 2 was irradiated with 365 nm ultraviolet light for 60 minutes to obtain a CsPbBr3 quantum dot solution modified with MMeS trimer (denoted as Mc-CPB).

[0048] Example 4

[0049] The present embodiment provides a composite of poly-HDDA dispersed CsPbBr3 quantum dots, and the preparation method thereof comprises the following steps: the M-CPB quantum dot solution prepared in Example 2 is mixed with 1,6-hexanediol diacrylate (HDDA) at a volume ratio of 4:1, a diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide photopolymerization catalyst of 1% by mass of HDDA is added, and the composite is heated at 3 mW / cm2 under the conditions of magnetic stirring at 200 r / min and nitrogen filling. 2 The mixed solution was irradiated with 365 nm ultraviolet light for 2 minutes to obtain a CsPbBr3 / poly-HDDA composite solid (denoted as MH-CPB).

[0050] Unless otherwise specified, the reactions in Examples 1-4 were all carried out at room temperature.

[0051] Application Example 1

[0052] The green light CsPbBr3 / poly HDDA complex prepared in Example 4 was mixed with red light KSF (K2SiF6: Mn 4+) The phosphor is mixed in the UV curing glue, stirred evenly and then dripped onto the 460nm blue light LED chip, and cured under UV light to obtain the white light LED lamp bead.

[0053] Application Example 2

[0054] The M-CPB perovskite quantum dots prepared in Example 2 were mixed with HDDA and n-dodecane in a ratio of 1:1:1 as ink, which was injected into an inkjet printing needle to print a regular text pattern of "Lanzhou University" and a relatively irregular frog graphic pattern on a silicon substrate material.

[0055] Test Example 1

[0056] a. Gel chromatography test

[0057] The reaction product of Example 1 was tested by gel chromatography. Figure 1 As shown, only a strong signal of 707 g / mol is shown, which is close to the molecular weight of the MMeS trimer, indicating that the reaction product of Example 1 is mainly the MMeS trimer, and also indicating that the sample Mc-CPB prepared in Example 3 is CsPbBr3 quantum dots modified with MMeS trimers.

[0058] b. XRD characterization

[0059] The samples prepared in Example 2-4 were characterized by X-ray diffraction (XRD). Figure 2 As shown. Sample M-CPB prepared in Example 2 and sample Mc-CPB prepared in Example 3 were used as comparative samples for sample MH-CPB prepared in Example 4. The diffraction peaks of M-CPB and Mc-CPB are completely consistent with the cubic phase of CsPbBr3 (PDF#54-0752) and there is no impurity phase, indicating that the products are all good single-phase samples. In the XRD diffraction pattern of sample MH-CPB prepared in Example 4, a broad diffraction peak due to the influence of the polymer appeared, but the characteristic diffraction peak belonging to the cubic phase CsPbBr3 crystal plane can still be observed at 30.04°, which shows that the polymerization reaction involving M-CPB does not destroy the original crystal structure of the quantum dots.

[0060] c. TEM characterization

[0061] The samples prepared in Examples 2-4 were characterized by transmission electron microscopy (TEM). Figure 3As shown. Samples M-CPB prepared in Example 2 and sample Mc-CPB prepared in Example 3 both present non-aggregated cubes, indicating that the use of the short-chain ligand MMeS does not cause the shape change of the CsPbBr3 quantum dots, and the modification of the MMeS trimer does not cause the shape change of the CsPbBr3 quantum dots. For the sample MH-CPB prepared in Example 4, it can be clearly seen that the CsPbBr3 quantum dots are uniformly dispersed in the polymer matrix, and the quantum dots in the polymer matrix do not aggregate, indicating that the in-situ crosslinking of MMES and HHDA is conducive to uniformly coating the quantum dots in the generated polymer matrix. From the high-resolution transmission electron microscopy image ( Figure 3 It can be clearly seen in the right column that the (110) crystal plane spacing of CsPbBr3 in M-CPB is 0.39nm, the (110) crystal plane spacing of CsPbBr3 in Mc-CPB is 0.40nm; the (220) crystal plane spacing of CsPbBr3 in MH-CPB is 0.24nm, which also proves the generation of CsPbBr3 quantum dots in each material.

[0062] d. Fluorescence emission characterization

[0063] The fluorescence emission spectra of the samples prepared in Example 2-4 are as follows: Figure 4 As shown. The emission peak of the sample M-CPB prepared in Example 2 is at 513nm; the emission peak of the sample Mc-CPB prepared in Example 3 slightly moves to 515nm; when CsPbBr3 quantum dots and HDDA are copolymerized into a solid polymer, the sample MH-CPB prepared in Example 4 has an emission peak of 516nm and an emission half-peak width of 19nm.

[0064] e. Characterization of water stability

[0065] The samples prepared in Examples 2-4 were immersed in water for different periods of time to test the changes in the fluorescence emission intensity of the samples. Figure 5 As shown, after immersion in water for 17 days, the fluorescence emission intensity of the sample MH-CPB prepared in Example 4 remained at 72% of its initial intensity, while the fluorescence emission intensities of its comparative samples M-CPB perovskite quantum dots prepared in Example 2 and Mc-CPB perovskite quantum dots prepared in Example 3 decreased to 0% and 18% of the initial fluorescence emission intensity, respectively, indicating that the dense polymer formed by HDDA in MH-CPB provides good physical protection for CsPbBr3 quantum dots, effectively avoiding the decomposition of quantum dots by water.

[0066] f. Thermal stability characterization

[0067] The samples prepared in Examples 3 and 4 were heated and the changes in the fluorescence emission intensity of the samples were tested in the temperature range of 298K to 358K. Figure 6It is shown that during the entire heating process, the relative value of the fluorescence emission of the sample MH-CPB prepared in Example 4 has been decreasing at a slower rate than that of the sample Mc-CPB perovskite quantum dots prepared in Example 3, showing a relatively high fluorescence thermal quenching performance. At 358K, MH-CPB maintained 22.3% of its initial intensity, while its counterpart Mc-CPB perovskite quantum dots only maintained 14.1%. This shows that the polymerization of HDDA with the M-CPB perovskite quantum dots prepared in Example 2 effectively reduces the shedding of ligands, thereby enhancing the thermal stability of the perovskite quantum dots.

[0068] g. White light LED lamp performance characterization

[0069] The white light LED lamp bead prepared in Application Example 1 can emit blue, green and red light at 460nm, 520nm and 631nm respectively to form a composite white light under a driving current of 10mA ( Figure 7 ), the color temperature of the LED lamp is 9014K, the luminous efficiency is 46.62lm / W, and the CIE coordinates are as follows Figure 8 It is shown as (0.2939, 0.3062) and covers 128% of the National Television System Committee (NTSC) color gamut ( Figure 8 The black triangle in the figure shows that this material can be applied to fields such as LED backlight display. In the driving current range of 10-80mA, as the current increases, the shape of the lamp bead emission peak remains relatively unchanged ( Figure 7 ), indicating that the photothermal stability of the sample MH-CPB prepared in Example 4 has a positive contribution to the working stability of the LED device.

[0070] h. Micropattern array characterization

[0071] like Fig. 9 As shown in the figure, the "Lanzhou University" perovskite micro-pattern array printed by using the ink prepared by M-CPB perovskite quantum dots prepared in Example 2 and HDDA and n-dodecane is about 1 cm long, and each luminous pixel point is a regular circle with a diameter of about 10 μm; at 3 mW / cm 2 Under 365nm ultraviolet light, the micro pattern and each pixel emit light evenly and stably, and can be matched with micro ultraviolet or blue light chips to be suitable for the construction of Micro-LED micro display devices.

[0072] Fig.10 The upper and lower layers are frog patterns printed with this ink at 3mW / cm 2, 365nm ultraviolet radiation polymerization and optical photos of polymerization without ultraviolet radiation. After four days of storage in an atmospheric environment (22°C, 55% humidity), the pattern polymerized by ultraviolet radiation still maintained strong luminescence, while the pattern polymerized without ultraviolet radiation retained only very weak luminescence. This shows that the photopolymerization process of M-CPB perovskite quantum dots prepared using HDDA and Example 2 significantly improves the environmental stability of the printed array.

[0073] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing cross-linked ligand-modified perovskite quantum dots, characterized in that: The functional molecule mono-2-(methacryloyloxy)ethyl succinate containing carboxyl and methacrylate groups was used as the ligand of perovskite quantum dots. The cesium lead precursor solution was injected into the xylene solution using the room temperature ligand-assisted reprecipitation method to grow CsPbBr3 perovskite quantum dots modified with the functional ligand MMeS. The methacrylate group in the MMeS molecule was then photopolymerized with the acrylic ester polymer monomer 1,6-hexanediol diacrylate to prepare the CsPbBr3 / poly-HDDA complex.

2. The method for preparing cross-linked ligand-modified perovskite quantum dots according to claim 1, characterized in that: The method comprises the following steps: (1) Preparation of CsPbBr3 perovskite quantum dots modified with functional ligands 1.1) adding cesium bromide, lead bromide, oleylamine and succinic acid mono-2-(methacryloyloxy)ethyl ester to N,N-dimethylformamide and stirring until the powder is completely dissolved to prepare a precursor solution; 1.2) Inject the precursor solution into a continuously stirred xylene solution to obtain a bright green solution; 1.3) After the solution obtained in step 1.2) is stirred for reaction, methyl acetate is added to generate a precipitate, and the precipitate is dispersed in xylene by centrifugation. The supernatant is collected by centrifugation to obtain a xylene solution of CsPbBr3 quantum dots modified with MMeS; (2) Preparation of CsPbBr3 / poly-HDDA complex by copolymerization of ligand and monomer The MMeS-modified CsPbBr3 quantum dot xylene solution obtained in step 1.3) was uniformly mixed with 1,6-hexanediol diacrylate, and diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide was added. Under stirring and nitrogen atmosphere, the solution was continuously irradiated with 365 nm ultraviolet light to obtain a CsPbBr3 / poly-HDDA composite solid.

3. The method for preparing cross-linked ligand-modified perovskite quantum dots according to claim 2, characterized in that: In step 1.1), the usage ratio of cesium bromide, lead bromide, oleylamine, mono-2-(methacryloyloxy)ethyl succinate, and N,N-dimethylformamide is 50-100 mg: 100-150 mg: 0.5-1 ml: 0.5-2 mmol: 5-10 mL.

4. The method for preparing cross-linked ligand-modified perovskite quantum dots according to claim 3, characterized in that: In step 1.2), the volume ratio of the precursor solution to the xylene solution is 0.5-1:5-10.

5. The method for preparing cross-linked ligand-modified perovskite quantum dots according to claim 4, characterized in that: In step 1.3), the stirring reaction time is 40 minutes; the volume ratio of ethyl acetate to xylene in step 1.2) is 1:1; the centrifugal speed is 12000 r / min when separating the precipitate, and the centrifugal speed is 8000 r / min when collecting the MMeS-modified CsPbBr3 quantum dot xylene solution.

6. The method for preparing cross-linked ligand-modified perovskite quantum dots according to claim 5, characterized in that: In step (2), the volume ratio of the MMeS-modified CsPbBr3 quantum dot xylene solution to 1,6-hexanediol diacrylate is 4:1, the amount of diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide is 1% of the mass of 1,6-hexanediol diacrylate; the intensity of the ultraviolet light is 3 mW / cm 2 The UV light irradiation time is 0.5 to 2 minutes.

7. MMeS-modified CsPbBr3 perovskite quantum dots and CsPbBr3 / poly-HDDA complexes obtained according to the method of any one of claims 1 to 6.

8. Application of the CsPbBr3 / poly-HDDA complex described in claim 7 in white light LEDs, and application of MMeS-modified CsPbBr3 perovskite quantum dots in electrofluidic inkjet-printed perovskite micro-pattern arrays.